PRICE FLUCTUATIONS AND VOLATILITY OF NATIONAL STRATEGIC FOOD COMMODITIES IN INDONESIA - Matondang, Muhammad Ridwansyah; Krisnamurthi, Bayu; Herawati, Herawati (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Meeting the food needs of the Indonesian population is a top priority, and national strategic food plays a vital role in achieving this goal. However, the unstable nature of national strategic food prices can have significant implications, particularly for those with low incomes. This volatility can hinder access to healthy and nutritious food, ultimately impacting the nation's food security. In recent times, food prices have risen sharply, which is expected to have far-reaching consequences. Therefore, it is imperative to analyze the volatility of national strategic food prices to comprehend price fluctuations and patterns. This study analyzed the volatility of national strategic food prices in Indonesia from 2018 to 2022, focusing on commodities such as shallots, garlic, red chilies, cooking oil, and rice. The ARCH-GARCH method used to conduct the analysis, revealing that all five commodity prices were volatile at the national level. The red chili and shallot exhibits a distinctive pattern, characterized by an increase volatility during the second quarter of each year. This can be attributed to the rise in demand during the Ramadan. Conversely, garlic volatility was high in early 2019 and 2020, while remaining relatively stable during other periods. Cooking oil volatility remained stable until the end of 2020, but started to increase in early 2021. This closely related to cooking oil crisis that occurred in Indonesia. Lastly, rice price volatility was high in early 2018. Subsequently, exhibited relatively stable volatility until first quarter of 2022, although there were some periods where the volatility exceeded its average.